Change – social and personal: Thomas and Znaniecki’s The Polish Peasant for the study of present-day change in global higher education - Joseph C. Hermanowicz, (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2019)
The present work represents an extrapolation of W.I. Thomas and Florian Znaniecki’s study, The Polish Peasant in Europe and America, on behalf of the development of sociological theory. The article focuses on careers and institutions in higher education. The curriculum vitae serves as the novel human document by which to investigate both social and personal change. Academic careers are studied by virtue of their objective and subjective dimensions. Objectively, the institution of education is revealed through the shifting expectations that govern work in academia in specific historical times (indicated by the cohort in which academics earned their Ph.D.s) and in specific socially bound places (indicated by the type of university in which academics work). Major social change in education is likely to spell personal change for the way in which people subjectively experience the contemporary academic career. The data come from U.S.-based academics; parallel transformational changes are observable globally. The global change discussed in the work centres on the diffusion and institutionalization of the research role. The sources and consequences of this change are problematic. Akin to Thomas and Znaniecki’s larger analytic aims, patterns of change are used inductively to formulate theory: the paper culminates by postulating a theory of increasing tendencies in the way knowledge is produced in higher education institutions throughout the world.